The optimal structure of capital with contingent claims: a case study in Colombia (2011)
One of the debates of the research of the Financial Economics relates to the existence or not of an ideal structure of capital that contributes value to the company. About thematter, several authors have studied the topic but without a consensus. It is illustrated, from the theories that follow the existence of an optimal capital structure, a model that determines it using the last developments in valuation of debt, such as the theory of contingent claims, based on the theory of options, for which uses information froma Colombian company.